Increasing precipitation promoted vegetation growth in the Mongolian Plateau during 2001–2018 - Li, Chuanhua; Li, Liangliang; Wu, Xiaodong; Tsunekawa, Atsushi; Wei, Yufei; Liu, Yunfan; Peng, Lixiao; Chen, Jiahao; Bai, Keyu (Frontiers in Environmental Science, 2023)
Climate warming largely promotes the vegetation growth in the temperature-limited ecosystems, while the warming-induced drought may inhibit vegetation growth in the arid and semi-arid regions, and it largely remains unknown about the effects of climate change on vegetation growth in the cold and arid regions. Here, we selected the Mongolian Plateau as study area to examine the vegetation growth during 2001-2018. We quantified the vegetation growth changes based on changes in gross primary productivity (GPP) and leaf area index (LAI) and their relationships to climate variables using correlation analysis, partial correlation analysis and multiple correlation analysis. The results showed that from 2001 to 2018 both GPP and LAI showed an increasing trend, with great heterogeneities among different areas and land cover types. The largest increase of GPP and LAI occurred in the northeast plateau with the land cover types of forest and cropland. The main driving factor of vegetation growth was precipitation, while temperature was significantly negatively correlated with vegetation growth. The CO2 concentration had a significant impact on the GPP in farmland, and the increase of solar radiation had a significant impact on tundra. Our study highlights the importance of precipitation in regulating vegetation growth in the Mongolian Plateau, challenging the prevailing views that the temperature dominates the vegetation growth in the northern ecosystems.